Keterbukaan Pelaku Usaha Millenial Terhadap Ekonomi Digital dalam Kegiatan Pemasaran - Muhammad Hasan; Miranda Miranda; Andi Asti Handayani; Nuraisyiah Nuraisyiah; Nurdiana Nurdiana (UNIVED Press, 2022)
This study aims to explore and analyze the form of openness of millennial business actors to the digital economy, primarily as a support for marketing activities. This study is a quantitative approach study using survey techniques. Data collection uses an instrument in the form of a questionnaire by millennials who have businesses. The sample used in this study was determined using a purposive sampling technique as many as 32 people who have met the criteria that have been set. The results of this study indicate the openness of millennial business actors to the digital economy as a support in marketing activities. The millennial generation is a generation that is very familiar with the use of technology so it is not difficult to adapt to the digital economy. This research has implications for awareness about the importance of using technology to support business activities.